THE INFLUENCE OF EXPERIENTIAL MARKETING AND TOURIST SATISFACTION ON TOURIST REVISIT INTENTION AT BUKIT KASIH KANONANG - Victoria Rorimpandey; Willem J. F. A Tumbuan; Ferdinand J. Tumewu (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
The development of tourism is currently fast. Tourism is one industry that can support a region’s economy. Tourism will provide a lot of income for regions that are aware of the potential for the tourism sector. The existence of regional autonomy makes each region try to exploit the potential of its region. Every region seeks to contribute to making tourism oriented towards improving the welfare of the local community.Increasingly fierce competition becomes a challenge and a threat for business actors in order to win the competition, maintain the market they have, and seize the existing market.The purpose of this study is to find out whether The Influence of Experiential Marketing and Tourist Satisfaction on Tourist Revisit Intention at Bukit Kasih Kanonang. This study uses quantitative method and the researchers distributed questionnaires and samples used 100 respondents. The results of this study found that experiential marketing and tourist satisfaction partially had a significant positive effect on tourist revisit intention at Bukit Kasih Kanonang and the results also showed that experiential marketing and tourist satisfaction simultaneously had a positive and significant effect on tourist revisit intention.